The Unexpected Love Objects of Dunya Noor : a Novel. - Haddad, Rana (The American University in Cairo Press, 2018)
Aspiring photographer Dunya Noor discovers early on that her curious spirit, rebellious nature, and very curly hair are a recipe for disaster in 1980s Syria. Many years later in London, she meets Hilal, the son of a humble tailor from Aleppo and no match for Dunya, daughter of the great heart surgeon Joseph Noor. But, dreamy, restless Dunya falls in love with Hilal and they decide to return to Syria together, embarking on a journey that will change them both forever. Rana Haddad's vivid and satirical debut novel captures the essence of life under the Assad dictatorship, in all its rigid absurd.